COPING SELF EFFICACY AND RESPONSE TO UNCERTAINTY IN THE COVID-19 PANDEMIC - Sarry, Septi Mayang; Anggreiny, Nila; Mafaza, Mafaza; Adilbayeva, Ulzhalgas Bikenovna (Insight: Jurnal Ilmiah Psikologi, 2021)
The COVID-19 pandemic creates uncertainty in various aspects of people's lives, especially when they enter adulthood with more complex roles and responsibilities. This study aims to measure the relationship of coping self-efficacy and individual responses in facing uncertainty. This study was conducted on 204 participants in the range of early adulthood (M = 27 years) which were taken based on quota sampling technique. The instrument used in this research is The Uncertainty Response Scale and Coping Self - Efficacy Scale. Based on the results of the analysis, Pearson Product Moment, it is found that there was a significant relationship between the response to uncertainty and coping self-efficacy. The relationship between the two variables is explained based on the three dimensions of the response to uncertainty: there is a significant negative relationship between the response to emotional uncertainty and coping self-efficacy; there is a significant positive relationship between cognitive uncertainty and desire for change and coping self - efficacy. The dimension of cognitive uncertainty showed stronger relationships while the dimension of desire for change showed weak relationships with coping self efficacy.